Stock market co-movement and exchange rate flexibility: Experience of the Republic of Korea - Yung Chul Park; Hail Park (Asian Development Bank Institute (ADBI), 2014)
This paper argues that for countries where equity investments dominate cross-border capital flows, the proper framework for analyzing the role of a flexible exchange rate system as a buffer against external shocks is the uncovered stock return parity condition, rather than the uncovered interest parity condition. Estimation of the stock return parity condition shows that it fails to hold in the Republic of Korea largely because of co-movement in the Republic of Korea and United States stock markets. Three global factors are largely responsible for the co-movement: global financial integration, which may be generating a global financial cycle; acceptance of insensitivity of exchange risk by global equity investors; and domestic investors imitating the trading behavior of foreign equity investors.
Keywords: F31; F65; G15; 330; free floating; uncovered interest rate and stock return parity conditions; currency risk; co-movement of stock prices